Effect of Al2O3, MgO, and CuOx on the dissolution behavior of rhodium in the Na2O-SiO2 slags - Wiraseranee C.; Yoshikawa T.; Okabe T.H.; Morita K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Aiming to optimize rhodium recovery in the high temperature recycling process by minimizing rhodium loss into slags in an oxidizing atmosphere by controlling slag composition, the effects of representative slag components, such as Al2O3, MgO, and CuOx, on the dissolution behavior of rhodium into the Na2O-SiO2 slags was investigated. The solubility of rhodium was measured by equilibrating the sodium silicate based slags with pure solid rhodium at 1473 K in air. Considering that rhodium dissolved into slags as RhO1.5, the effect of the oxide addition on the activity coefficient of RhO1.5 in slags was determined. The dissolution of rhodium in slags was suppressed by the addition of Al2O3 and MgO, where Al2O3 behaved as an acidic oxide and MgO behaved as a diluent of slag basicity at a fixed Na2O/SiO2 ratio of 0.97. The content of copper in solid rhodium equilibrated with the CuOx bearing slags slightly increased with increasing content of CuOx, and CuOx was found to slightly enhance the dissolution of rhodium. Rhodate capacity of all slag systems increased with increasing optical basicity, suggesting that the correlation between rhodate capacity and the optical basicity enables the estimation of the content of rhodium in slags of which thermodynamic properties of rhodium are not clarified.